Nilai-Nilai Edukatif Dalam Novel Ayah Karya Andrea Hirata: Tinjauan Sosiologi Sastra Dan Implementasinya Pada Pembelajaran Sastra Di SMA N 1 Sambungmacan - AYUNINGTYAS, RAHMAWATI; , Drs. Adyana Sunanda, M.Pd (2016)
The purpose of this study is (1) to describe the structure of the novel by Andrea Hirata's Ayah, (2) The values of Educational novel by Andrea Hirata's Ayah, (3) implementation of research novel by Andrea Hirata's Ayah to study of literature in SMA N 1 Sambungmacan. The method used is descriptive qualitative. The object of this research is the educational values in the novel Ayah. Data used in the form of sentences and paragraphs contained in the novel's Ayah. Sources of primary data in this study is a novel Ayah Andrea Hirata, published by the Bentang Pustaka. Sources of secondary data in this study using the book entitled "Wisata Hemat Belitung" written by Endah Murniwati published by PT Elex Media Komputindo. Data collection techniques using literature techniques, see and and record. Data analysis techniques in this study using dialectics. The validity of the data used is data triangulation. Based on the analysis of the structure, the theme of the novel's Ayah is affection between a father and child, in addition to the novel's father was also the theme of friendship. Flow used in the novel's Ayah is the flow of the mixture. figures analyzed are Sabari, Marlena, Ukun, Tamat, Zorro, Toharun, Zuraida, Izmi, Markoni, Insyafi, Bu Norma, Manikam, Jon Pijareli, and Amirza. Background story used in Ayah novel consists of a background, the background of the time, and sociocultural background. Educational value contained in the novel's Ayah is a moral value, the value of cooperation or mutual help, the religious values, values of responsibility, the value of love and the value of discipline. The results of the study novel Ayah Andrea Hirata can be implemented in the instructional literature in SMA N 1 Sambungmacan.